2014
DOI: 10.1038/ncomms6788
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical predictions for hot-carrier generation from surface plasmon decay

Abstract: Decay of surface plasmons to hot carriers finds a wide variety of applications in energy conversion, photocatalysis and photodetection. However, a detailed theoretical description of plasmonic hot-carrier generation in real materials has remained incomplete. Here we report predictions for the prompt distributions of excited ‘hot’ electrons and holes generated by plasmon decay, before inelastic relaxation, using a quantized plasmon model with detailed electronic structure. We find that carrier energy distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
789
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 669 publications
(842 citation statements)
references
References 39 publications
32
789
0
4
Order By: Relevance
“…Hot carriers are primarily generated with momentum parallel to the external field [31], which is generally parallel with the semiconductor interface in the case of an antenna, resulting in poor injection. Moreover, hot electron generation is also dependent on the plasmonic material employed [32,72,[76][77][78]. Several groups have explored the effects of the electronic structure of the metal on the generated carrier distributions [32,76] ( Figure 1F), and it has been shown that, in the interband transition regime, the electronic band structure of the metal plays an important role in determining both the energy and the momentum distribution of the generated hot carriers [32].…”
Section: Hot Carrier Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hot carriers are primarily generated with momentum parallel to the external field [31], which is generally parallel with the semiconductor interface in the case of an antenna, resulting in poor injection. Moreover, hot electron generation is also dependent on the plasmonic material employed [32,72,[76][77][78]. Several groups have explored the effects of the electronic structure of the metal on the generated carrier distributions [32,76] ( Figure 1F), and it has been shown that, in the interband transition regime, the electronic band structure of the metal plays an important role in determining both the energy and the momentum distribution of the generated hot carriers [32].…”
Section: Hot Carrier Generationmentioning
confidence: 99%
“…Hot electron transfer efficiencies can further be boosted by embedding the plasmonic nanostructures within the semiconductor, providing more momentum space for hot electron emission [86] (Figure 7A). In addition, it has been shown that the preferred carrier type for extraction, either electrons or holes, is dependent on the plasmonic material employed [32,72].…”
Section: -156mentioning
confidence: 99%
See 1 more Smart Citation
“…There exists a pathway of photoinduced charge transfer from the semiconductor to the metal, which can be used to controllably vary the driving forces at the interface that leads to tunable optoelectronic properties. In this letter, we report the observation of a dramatic suppression of plasmonic as well as excitonic absorption in a-Ge 24 Exciton-plasmon coupling in a semiconductor/metallic hybrid structure can generate promising opportunities for new optical functionalities that are feasible with neither of the individual components of coupled states. 1,2 Although the coupling between the two quasi-particles, viz., plasmons and excitons are not yet fully understood, it is accepted that the surface plasmons in metal nanoparticles can trap and guide light at the nanoscale over broad spectral ranges.…”
mentioning
confidence: 99%
“…15,16 As a result, we have an outstanding problem connecting the optical nonlinearity of excitons, which defines their photosensitivity, with the field enhancement shown by the plasmons. In this letter, we demonstrate plasmon-exciton interaction at the ultrafast time scale in an amorphous Ge 24 Se 76 /gold nanoparticle (AuNP) heterostructure, which can be controlled by varying the plasmon wavelength. Our studies show that the coupling in these heterostructures is strong enough such that the exciton and plasmon absorptions are dramatically quenched.…”
mentioning
confidence: 99%